APLIKASI REMOTE SENSING UNTUK PEMETAAN SEBARAN KEMISKINAN (Studi Kasus: Kelurahan Kledungkradenan, Kecamatan Banyuurip, Kabupaten Purworejo, Provinsi Jawa Tengah) - Akhmad Fauzy; Sus Budiharto; Anggara Setyabawana Putra (Asian Journal of Innovation and Entrepreneurship, 2016)
Poverty is one of the very complex problems in some community. Poverty is affected by many factors, including environmental, health, income, and location of residence. Therefore, it is necessary to reduce poverty appropriately. According to the Indonesian Presidential Regulation No. 13 Year 2009 on Poverty Reduction Coordination, Article 1, on poverty reduction policies and programs of the government and local authorities conducted a systematic, planned, and synergy with the business community and the public to reduce the number of poor people in order to increase the degree of people welfare. Map of Distribution Poverty, is one prototype map, which can be used to display data based on spatial poverty. Poverty data is usually displayed in the form of numbers or index, can be displayed in the map sheet or visualized, making it easier to understand the conditions of poverty in the community. Mapping is done with a detailed scale of 1: 5000, with the data source satellite imagery in Kledungkredenan, Banyuurip, Purworejo, Central Java Province.